2012
DOI: 10.1002/anie.201205351
|View full text |Cite
|
Sign up to set email alerts
|

Strophasterols A to D with an Unprecedented Steroid Skeleton: From the Mushroom Stropharia rugosoannulata

Abstract: The mushroom Stropharia rugosoannulata is called saketsubatake in Japanese, and wine-cap stropharia in English. It belongs to the family Strophariaceae, which is widespread in northern temperate zones throughout the world. It is edible and is cultivated for food. During screening for anti-endoplasmic-reticulum (ER) stress and anti-methicillin-resistant Staphylococcus aureus (MRSA) effects of the extracts of various mushrooms, we found activity in the extract of this mushroom. ER stress induces apoptotic pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
56
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 3 publications
0
56
0
2
Order By: Relevance
“…[3] Thep resenilins (6-8 transmembrane proteins) are mainly localized to the endoplasmic reticulum, where they are part of the g-secretase protein complex that cleaves APP to generate Ab peptides.T he resulting amyloidogenic peptides can damage neurons by inducing membrane-associated oxidative stress,t hereby rendering neurons vulnerable to Ca 2+ overload, particularly under conditions of impaired mitochondrial energy production. [6] While the structures of the former two (strophasterols Aand B, 1A and 1B)h ave been unequivocally determined by singlecrystal X-ray diffraction, [7] thes tructures of strophasterols C and D( 1C and 1D)r emain uncertain with regard to their relative and absolute configuration. [5] Strophasterols A-D (1A-D;F igure 1), four secosterols with an unprecedented carbon skeleton, have recently been isolated from the mushroom Stropharia rugosoannulata, which is abundant in the northern temperate zone.…”
mentioning
confidence: 99%
“…[3] Thep resenilins (6-8 transmembrane proteins) are mainly localized to the endoplasmic reticulum, where they are part of the g-secretase protein complex that cleaves APP to generate Ab peptides.T he resulting amyloidogenic peptides can damage neurons by inducing membrane-associated oxidative stress,t hereby rendering neurons vulnerable to Ca 2+ overload, particularly under conditions of impaired mitochondrial energy production. [6] While the structures of the former two (strophasterols Aand B, 1A and 1B)h ave been unequivocally determined by singlecrystal X-ray diffraction, [7] thes tructures of strophasterols C and D( 1C and 1D)r emain uncertain with regard to their relative and absolute configuration. [5] Strophasterols A-D (1A-D;F igure 1), four secosterols with an unprecedented carbon skeleton, have recently been isolated from the mushroom Stropharia rugosoannulata, which is abundant in the northern temperate zone.…”
mentioning
confidence: 99%
“…2 In further research, we discovered two novel sterols. Herein, we describe the isolation and structure determination of the compounds from the mushroom.…”
Section: Introductionmentioning
confidence: 94%
“…Wu et al [61,62] reported the isolation of four new sterols having a very unique and unprecedented carbon skeleton, strophasterols A-D (95-98), from the fruiting bodies of Stropharia rugosoannulata (Fig. 1.15).…”
Section: Sterols Bearing 5a6a-epoxy Groupmentioning
confidence: 99%
“…1.15). In a protective activity assay against ER-stress-dependent cell death caused by tunicamycin or thapsigargin, none of the compounds showed any inhibitory effect on tunicamycin toxicity, but compound 95 showed a dose-dependent inhibitory effect on thapsigargin toxicity (increase in cell viability compared with control, 10.3%) [61]. Compounds 95-98 were evaluated by endoplasmic reticulum (ER)-stress suppression and an anti-methicillinresistant Staphylococcus aureus (MRSA) assay.…”
Section: Sterols Bearing 5a6a-epoxy Groupmentioning
confidence: 99%
See 1 more Smart Citation